Combined Pituitary Hormone Deficiency and PROP-1 Mutation in Two Siblings: A Distinct MR Imaging Pattern of Pituitary Enlargement - do Amaral, L.L.F.; Ferreira, R.M.; Ferreira, N.P.F.D.; Mendonça, R.A.; Marussi, V.H.R.; da Cunha, J.L.; Maçaranduba, B.R.; Medeiros, J.D. (American Journal of Neuroradiology, 2007)
SUMMARY: Mutations of the PROP-1 gene are the most frequent genetic defect in patients with combined pituitary hormone insufficiency. We present the cases of 2 siblings with PROP-1 mutations whom we observed longitudinally. Their initial pituitary MR imaging examinations showed identical findings: an enlarged adenohypophysis, with striking hypointensity on T2-weighted images and slight hyperintensity on T1-weighted images. In one of the children, the follow-up MR imaging obtained 3 years after hormonal replacement revealed a decrease in the size of the anterior pituitary lobe.